Analysis of Factors Causing Variation Order In Construction Projects of PT. Tatamulia Nusantara Indah Surabaya Branch Office 2018-2022 Period - Ali Imron, Mohammad; Teki Tjendani, Hanie; Witjaksana, Budi (Green Publisher Indonesia, 2022)
One of the significant problems that occur during the construction management process of a project is the scope change or variation orders. Based on this background, the research problem is regarding the factors causing the change in scope (variation order). The research objective was to analyze the partial influence of consultant incompetence and material problems on variation orders. The research was conducted at the Grand Mercure Malang Hotel and the research will be carried out in 2022. The measurement of the five research variables is a subjective measurement. Related to this research, 25 previous studies that are relevant to the 2016-2021 publication period are described. The theoretical basis presented is variation order, consultant incompetence, and material problems. The research hypothesis is that the two independent variables are partially thought to influence variation order. Quantitative research approach. The research location is at the Grand Mercure Malang Hotel in Malang – East Java. The time of the research is a one-time study, namely 2022. The research population is all employees who are directly related to construction projects. The sampling technique uses non-probability sampling, in this case incidental sampling. Data collection techniques through surveys. The research instrument was a questionnaire with a Likert scale of 1-6. Data analysis techniques include descriptive analysis techniques, and SEM-PLS. The results of the study show that the incompetence of consultants and material problems partially affect the Variation Order positively and significantly